Flood-Prone Area Mapping Using the Integration of Hydrological Data and Google Earth Engine (GEE) - Firman Pindria; Jonni Mardizal (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Flood susceptibility mapping that integrates hydrological and geospatial information remains limited at the sub-watershed scale, particularly in rapidly developing coastal urban areas. This study maps flood susceptibility in the Batang Kandis Sub-watershed, Padang City, by integrating hydrological data through Google Earth Engine (GEE). A quantitative spatial approach was employed using six parameters: rainfall, elevation, slope, soil texture, land cover, and proximity to rivers. Each parameter was classified, scored, and weighted using the Analytic Hierarchy Process (AHP), after which a weighted overlay was applied to generate the Flood Susceptibility Index (FSI). The results indicate that 58.77% of the study area is classified as having very high flood susceptibility, while 21.39% is classified as highly susceptible. These zones are concentrated primarily in downstream areas characterized by low elevations, gentle slopes, extensive built-up surfaces, and close proximity to river networks. Validation against historical inundation data from Ina-Geoportal demonstrated 97.10% spatial correspondence with areas classified as having high or very high susceptibility. These findings confirm that integrating hydrological and geospatial parameters through GEE provides a reliable approach to identifying flood-prone areas at the sub-watershed scale. The resulting susceptibility map provides an evidence-based foundation for prioritizing flood mitigation, strengthening watershed management, and supporting adaptive spatial planning in rapidly developing coastal urban areas.